Large effect of irradiance on hydrogen isotope fractionation of alkenones in Emiliania huxleyi. (1st July 2015) - van der Meer, Marcel T.J.; Benthien, Albert; French, Katherine L.; Epping, Eric; Zondervan, Ingrid; Reichart, Gert-Jan; Bijma, Jelle; Sinninghe Damsté, Jaap S.; Schouten, Stefan
Abstract: The hydrogen isotopic (δD) composition of long-chain alkenones produced by certain haptophyte algae has been suggested as a potential proxy for reconstructing paleo sea surface salinity. However, environmental parameters other than salinity may also affect the δD of alkenones. We investigated the impact of the level of irradiance on hydrogen isotopic fractionation of alkenones versus growth water by cultivating two strains of the cosmopolitan haptophyte Emiliania huxleyi at different light intensities. The hydrogen isotope fractionation decreased by approximately 40‰ when irradiance was increased from 15 to 200 μmol photons m −2 s −1 above which it was relatively constant. The response is likely a direct effect of photosystem I and II activity as the relationship of the fractionation factor α versus light intensity can be described by an Eilers–Peeters photosynthesis model. This irradiance effect is in agreement with published δD data of alkenones derived from suspended particulate matter collected from different depths in the photic zone of the Gulf of California and the eastern tropical North Pacific. However, haptophyte algae tend to bloom at relatively high light intensities (>500 μmol photons m −2 s −1 ) occurring at the sea surface, at which hydrogen isotope fractionation is relatively constant and not affected by changes in light intensity. Alkenones accumulating in the sediment are likely mostly derived from these surface water haptophyte blooms, when the largest amount of biomass is produced. Therefore, the observed irradiance effect is unlikely to affect the applicability of the hydrogen isotopic composition of sedimentary long chain alkenones as a proxy for paleosalinity.